Genetic mapping of QTLs controlling brown seed coat traits by genome resequencing in sesame (Sesamum indicum L.) - Wang, Han; Cui, Chengqi; Liu, Yanyang; Zheng, Yongzhan; Zhao, Yiqing; Chen, Xiaoqin; Wang, Xueqi; Jing, Bing; Mei, Hongxian; Wang, Zhonghua (Frontiers in Plant Science, 2023)
Sesame seeds have become an irreplaceable source of edible oils and food products with rich nutrients and a unique flavor, and their metabolite contents and physiological functions vary widely across different seed coat colors. Although the quantitative trait loci (QTLs) for genetic variation in seed coat color have been extensively investigated, the identification of unique genetic loci for intermediate colors such as brown has not been reported due to their complexity. Here, we crossed the white sesame ‘Yuzhi No. 8’ (YZ8) and the brown sesame ‘Yanzhou Erhongpi’ (YZEHP) to construct a recombinant inbred line (RIL) population with consecutive self-fertilization for ten generations. The selfed F1 seeds were brown which was controlled by a dominant gene. Based on the genotyping by whole-genome resequencing of the RILs, a major-effect QTL for brown coat color was identified through both bulk segregant analysis (BSA) and genetic linkage mapping in sesame, which was located within a 1.19 Mb interval on chromosome 6 (qBSCchr6). Moreover, we found that the YZEHP seed coat initially became pigmented at 20 days post-anthesis (DPA) and was significantly colored at 30 DPA. We screened 13 possible candidate genes based on the effects of genetic variants on protein coding and predicted gene functions. Furthermore, qRT‒PCR was used to verify the expression patterns of these genes in different post-anthesis developmental periods. We noted that in comparison to YZ8 seeds, YZEHP seeds had expression of SIN_1023239 that was significantly up-regulated 2.5-, 9.41-, 6.0-, and 5.9-fold at 15, 20, 25, and 30 DPA, respectively, which was consistent with the pattern of brown seed coat pigment accumulation. This study identified the first major-effect QTL for the control of the brown seed coat trait in sesame. This finding lays the foundation for further fine mapping and cloning as well as investigating the regulatory mechanism of seed coat color in sesame.